The effects of climate change: an overview of the ecological and economic consequences (Journal of Forestry, 2024)
Climate change, a relentless force of nature, poses a significant threat to ecosystems and endangers livelihoods. This review examines the diverse impacts of climate change, ranging from shifting seasons and retreating glaciers to rapidly rising sea levels. These changes lead to identifiable risks such as rising temperatures, dwindling groundwater supplies, loss of biodiversity, reduced forestry and agricultural productivity, and increased health risks. The impacts go beyond the ecological sphere and permeate global economies. Particularly important is the disproportionate impact on countries with limited resources and lower socio-economic status. In addition, this report examines the complicated dynamics of international cooperation on climate policy, and underscores the urgent need for collective efforts to address the escalating environmental crisis. Carbon emissions are the main cause of global climate change. In response, the world's nations have come together under the Kyoto Protocol, which is based on the recognition of different national capacities to address climate-related challenges. The transition from the Kyoto Protocol to the Paris Agreement underscores the shift towards collective responsibility for climate change and emphasizes international cooperation and efforts to build resilience, particularly for the benefit of vulnerable nations. Therefore, this synthesis of systematic review procedures and bibliometric analysis methods underscores the need for coordinated action to mitigate the looming environmental crisis. Strategic planning and implementation are essential to proactively mitigate the negative effects of climate change. Efforts such as afforestation, reforestation and reducing dependence on fossil fuels, as well as the extensive use of renewable energy sources such as wind, solar and geothermal sources, offer significant potential to reduce greenhouse gas emissions.